Potential Sources of Modern Day Slavery - Dipietro, William (Advances in Social Sciences Research Journal, 2016)
Globally, the existence and persistence of slavery is a major problem that needs to be addressed. In addition to calling attention to slavery by making slavery a high priority issue on the national agenda, gaining some understanding of the sources of slavery is necessary for governments to effectively deal with slavery. This paper considers four factors as potential determinants of slavery at the national level. They are economic development, population growth, unemployment, and natural resource rental income. Empirically, cross country regression analysis is undertaken to test whether these four factors are of consequence for slavery. The results suggest that each of the four factors is relevant for slavery, with higher levels of economic development leading to lower levels of slavery, and higher population growth, unemployment, or rental income , leading to higher levels of slavery. It is appalling, but true, that slavery still exists in the modern world. From almost any moral perspective, or from practically any notion of what it means to be civilized, slavery, the ownership of one individual by another, is an abomination. One of the major feasts of the Jewish people, the Passover, celebrates the emancipation of the Jewish people from the cruel fate of slavery. From a Rawlsian point of view, welfare in society can be maximized by making the worst possible state in society as good as possible. As there is almost nothing worse that can be imagined than for a human being to be in slavery, this means, from a Rawlsian perspective, that social welfare is maximized by minimizing slavery. In order to reduce slavery, to be able to devise policies to effectively control slavery, it is first necessary to understand the current causes of slavery, and the conditions that bring it about . The nation state, at the present time, is the preeminent form of political and social organization. Across nations, the amount of slavery varies considerably. The fundamental question is why. What are the reasons for differences in the amount of slavery across nations? This paper investigates whether four potential factors, the level of economic development, population growth, unemployment, and, rent as a source of income are important in explaining differences in the amount of slavery between nations. The paper is broken down into five sections. The first section reviews some of the work that has been done looking at the sources of modern slavery. The second section presents a formal model of modern slavery. The third sections identifies the sources of the variables that are used in the empirical analysis. The fourth section discusses the results of cross country regressions of slavery on economic development and the three other variables considered as potential determinates of slavery. The fifth section closes by offering some concluding remarks.